Aliran Modal Portfolio dan Implikasinya terhadap Pergerakan Nilai Tukar: Studi Kasus Indonesia 1997-2007 - Perwitasari, Shinta Dewi; Falianty, Telisa A. (UI Scholars Hub, 2008)
As the result of global financial liberalization there is a tendency for increasing number of portfolio investment which in turn dominates the domestic financial market. This study aims to elaborate the effect of short- term portfolio investment flows to the exchange rate. Using the method of Vector Auto Regressive (VAR), this study employs quarterly data from 1997 to 2007. The result shows that both real and nominal exchange rates are affected by the short-term portfolio investment flows dominantly. In particular the short-term portfolio investment inflows strengthen the local currency. Secondly, in other direction short-term portfolio investment flows also affected by both real and nominal exchange rate. Thirdly, the impact of short- term portfolio investment flows to change of nominal exchange rate is temporarily due to adjustment toward equilibrium, but not for real exchange rate.